2014
DOI: 10.1097/mao.0000000000000316
|View full text |Cite
|
Sign up to set email alerts
|

Pars Tensa Retractions Without Cholesteatoma in Children

Abstract: Absence of correlation between stage of pars tensa retraction and air conduction thresholds with ossicular defects justifies surgical exploration of the auditory ossicles, even in lower stages of retraction. Combined ossicular defect is expected in combined retractions. The usage of cartilage graft proved to be more appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
(18 reference statements)
1
7
0
Order By: Relevance
“…However, the ABG's PTA was not a predictor of ossicular chain erosion. This corroborates with the existing data, which shows no correlation between hearing thresholds and the stages of retraction (11,14).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the ABG's PTA was not a predictor of ossicular chain erosion. This corroborates with the existing data, which shows no correlation between hearing thresholds and the stages of retraction (11,14).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we analyzed the behavior of retractions in all areas of TM, and we observed that the majority of retractions (64%) had an association with affected regions. Jesic et al (14) showed that the combination of PF and PT retractions in the same ear was a predictor of a long incus process and stapes superstructure erosion. However, the ABG's PTA was not a predictor of ossicular chain erosion.…”
Section: Discussionmentioning
confidence: 99%
“…One study 16 aimed to improve middle ear ventilation via ventilation tube insertion. As part of a prospective study 16 10 ears with combined tensa (Sade grades I–II) and flaccida (Tos grades I–IV) retractions underwent aeration tube insertion.…”
Section: Resultsmentioning
confidence: 99%
“…One study 16 aimed to improve middle ear ventilation via ventilation tube insertion. As part of a prospective study 16 10 ears with combined tensa (Sade grades I–II) and flaccida (Tos grades I–IV) retractions underwent aeration tube insertion. The authors report that out of the group of 10 ears (Sade grades I–II) with aeration tube insertion, seven had post‐operative retractions.…”
Section: Resultsmentioning
confidence: 99%
“…A normal tympanic membrane is tough and elastic, but the retraction pocket is flexible and collapses into the tympanic cavity. The place of weakness is most often located near the anatomical structures such as incisura Rivini, scutum or malleus [ 12 ]. It can affect both parts of the TM, pars tensa or pars flaccida.…”
Section: Introductionmentioning
confidence: 99%